2008
DOI: 10.1002/term.107
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible methodology for the isolation of mesenchymal stem cells from human umbilical cord and its potential for cardiomyocyte generation

Abstract: Mesenchymal stem cells (MSCs) are considered to be a source of stem cells in tissue regeneration and therapeutics, due to their ability to undergo proliferation and differentiation. Complications associated with bone marrow-derived MSCs has prompted researchers to explore alternative sources of MSCs. The human umbilical cord is one such source; it is easily available and its collection is non-invasive. The sources of MSCs are non-controversial and thus they are not subjected to ethical constraints, as in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 23 publications
2
50
0
Order By: Relevance
“…In contrast, hUC-MSCs retained a fibroblastic morphology until Cytotechnology ( 2016) 68:2061-2073 2069 passage 10 of the culture (data not shown). Although both MSCs were efficiently amplified under a standard culture condition (Pereira et al 2008;Hartmann et al 2010;Chong et al 2011), yet a prominent difference in term of doubling time and growth kinetics were noticed. Trypan blue and MTT assay clearly demonstrated that hUC-MSCs inherited a faster doubling time between 48 and 72 h than those of hC-MSC (*72 h).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, hUC-MSCs retained a fibroblastic morphology until Cytotechnology ( 2016) 68:2061-2073 2069 passage 10 of the culture (data not shown). Although both MSCs were efficiently amplified under a standard culture condition (Pereira et al 2008;Hartmann et al 2010;Chong et al 2011), yet a prominent difference in term of doubling time and growth kinetics were noticed. Trypan blue and MTT assay clearly demonstrated that hUC-MSCs inherited a faster doubling time between 48 and 72 h than those of hC-MSC (*72 h).…”
Section: Discussionmentioning
confidence: 98%
“…Beside the targeted differentiation, MSCs also migrate and home at the injured/inflamed tissues to expedite the tissue repair by secreting growth factors and harnessing the uncontrolled immune response (Kinnaird et al 2004;Pereira et al 2008;Ramasamy et al 2008). Under a specific inductive condition, MSCs are capable of differentiating into mesodermal lineage cells, including cardiomyocytes (Sanchez et al 2000;Deans and Moseley 2000;Forbes et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They adhere to plastic surfaces in vitro, are capable of spontaneous differentiation along the osteogenic, chondrogenic and adipogenic lineages and express a subset (but not all) of the surface markers of the skin and lung fibroblasts (Dominici et al 2006). Targeted differentiation of MSCs may yield other cell types as well, such as insulin-producing pancreatic cells, different kidney-specific cell types such as tubulocytes and podocytes, cardiomyocytes, and other cell types , Pereira et al 2008, Brunner et al 2008, Asanuma et al 2010. MSCs possess significant potential for use in the regenerative and reparative medicine because of their versatility.…”
Section: Potential Role Of Irc As a Factor Determining The Survival Omentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are self-renewing and multipotent cells, which have the potential to differentiate into various tissue cells, including osteoblasts (1,2), adipocytes, chondrocytes (3), neurons, glia cells (4), and cardiomyocytes (5), under favorable conditions. Owing to this potential, MSCs are being increasingly investigated for their use in cell-based regenerative medicine and tissue engineering (6).…”
Section: Introductionmentioning
confidence: 99%